LINKING BIG DATA TRAITS, DATA QUALITY DIMENSIONS AND BIG DATA ANALYTICS APPLICATION MODEL IN THE MALAYSIAN PUBLIC SECTOR - Zam Zarina Abdul Jabar (Tesis, 2024)
The primary goal of this research is to investigate the influences of BDT and DQD on BDA application within the Malaysian public sector, develop a model of their relationship and evaluate this model. This research included participants from 22 ministries and four Malaysian Government agencies.